LA TENSIÓN ENTRE EL MUNDO DEL TRABAJO Y LA POLÍTICA EDUCATIVA: JÓVENES Y ESCUELA SECUNDARIA EN ARGENTINA (2000-2014) | The tension between the world of work and the educational policy: young people and high school in Argentina (2000-2014) (Trabalho & Educação, 2018)
In the last decade in Argentina different investigations have registered an increase in the enrollment of high school level of the education system. The implementation of policies and legal mechanisms to the sector, open new questions to think about the link between education and work in the trajectories of youth. In this sense, the article seeks to contribute to the debate about the dynamics of the scope of secondary education during the period of 2000-2014 and the participation of young people in the labor market. The work focuses on the analysis of quantitative data from official sources that show the different tensions between high school enrollment and indicators of participation in the world of work. Data present challenges to think about the fulfillment of the educational policy objectives throughout the period analyzed. The article is part of the project: "Possible itineraries or probable itineraries: A study on educational and labor trajectories of young people from different social sectors, graduates of high school in Argentina", developed at the Latin American Faculty of Social Sciences (FLACSO), Argentina (2014-2017) with funding from the National Agency for Scientific and Technological Promotion (PICT / 2013 -0522) and in conjunction with the Universidad del Salvador (USAL). The empirical evidence allows us to return to the classic debates on the link between education and work and the sociology of education facing the discussions about the challenges presented by the period under analysis towards the equality of possibilities in the access, permanence and completion of secondary school and the effective employment opportunities available.___En la última década en Argentina distintas investigaciones han registrado una ampliación en la matricula del nivel medio del sistema educativo. La implementación de políticas y mecanismos legales hacia el sector, abren nuevas preguntas para pensar el vínculo educación y trabajo en las trayectorias juveniles. En este sentido, el artículo busca aportar al debate acerca de la dinámica del alcance de la educación media durante el periodo 2000-2014 y la participación de los jóvenes en el mercado de trabajo. El trabajo se centra en el análisis de datos cuantitativos de fuentes oficiales que muestran las distintas tensiones entre la matrícula escolar del nivel medio y los indicadores de participación en el mundo del trabajo. Datos que presentan desafíos para pensar en el cumplimiento de los objetivos de la política educativa a lo largo del periodo analizado. La presentación se enmarca en el proyecto: “Itinerarios posible o itinerarios probables: Un estudio sobre trayectorias educativas y laborales de jóvenes de distintos sectores sociales, egresados de la escuela media en Argentina”, desarrollado en la Facultad Latinoamericana de Ciencias Sociales (FLACSO), sede Argentina (2014-2017) con financiamiento de la Agencia Nacional de Promoción Científica y Tecnológica (PICT/2013 -0522) y en conjunto con la Universidad del Salvador (USAL). La evidencia empírica permite retomar los debates clásicos de la sociología de la educación afrontando las discusiones en torno a los desafíos que presenta el periodo bajo análisis hacia la igualdad de posibilidades en el acceso, permanencia y terminalidad de la escuela secundaria y las efectivas oportunidades de empleo disponibles.